Investigation of illness perception and pregnancy avoidance in sexually active women with epilepsy - Barut, Sumeyye; Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Aytacc, Emrah (Academic Press Inc Elsevier Science, 2023)
Aim: The aim of the study was to examine the perception of illness and avoidance of pregnancy in sexually active women with epilepsy. Methods: This study was completed with 82 women with epilepsy who were sexually active and who were admitted to the neurology clinic and outpatient clinic between June and September 2022. The descriptive information form, Brief Illness Perception Questionnaire (IPQ-B), and Pregnancy Avoidance Scale (PAS) were used to collect the data.Results: The mean age of the patients in the study was 32.96 & PLUSMN; 5.92 years and the mean disease duration was 11.19 & PLUSMN; 7.46 years. Among the patients, 75.6% had previous pregnancies, 70.7% did not have miscarriage or abortion, 69.5% previously gave birth, 61% used a contraceptive method (condom, intrauterine device (IUD), pills, etc.) in their last sexual intercourse, 52.4% had good communication with their spouses, 20% had two children, 51.2% had three or more seizures, and 86.6% used antiseizure medications (ASMs). The mean PAS score of the patients was 2.31 & PLUSMN; 1.14 and the mean IPQ-B score was 35.10 & PLUSMN; 13.16. The regression analysis found that the perception of illness was a significant positive predictor of avoidance of pregnancy and explained 17% of it.Conclusion: Women with epilepsy avoided pregnancy and had negative illness perceptions. Moreover, negative illness perception increased pregnancy avoidance in women with epilepsy.& COPY; 2023 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Sexually active woman; Illness perception; Pregnancy avoidance; Patient